Does vaccination with 4CMenB convey protection against meningococcal serogroup B strains not predicted to be covered by MATS? A study of the UK clonal complex cc269 - Maria Stella; Maria Giuliani; Alessia Biolchi; Sara Tomei; Rosita De Paola; Xilian Bai; Ray Borrow; Jay Lucidarme; Rita La Gaetana; Daniela Toneatto; Mariagrazia Pizza; Laura Serino; et al. (Human Vaccines & Immunotherapeutics, 2020)
The Meningococcal Antigen Typing System (MATS) has been developed as an hSBA surrogate to evaluate potential coverage afforded by the 4-component meningococcal serogroup B vaccine (4CMenB: Bexsero, GSK). We investigated whether the lower value of MATS coverage among invasive Meningococcus serogroup B clonal complex 269 strains from the United Kingdom (53% in 2014–2015 versus 73% in 2007–2008) reflected the lower bactericidal activity of the vaccine against these isolates. A total of 34 MATS-negative strains (31 were cc269 or closely related) were tested against pooled sera from 32 or 72 4CMenB-vaccinated infants in a serum bactericidal antibody assay in presence of human complement (hSBA). All infants had received four 4CMenB doses in the first 2 y of life. Baseline sera comprised 180 pooled samples from healthy-unvaccinated 2-month-old infants. Twenty of the 34 (59%) MATS-negative strains were killed in hSBA with titers ≥4 by pooled sera from vaccinated infants. There were 13/34 strains with hSBA titers ≥4 and at least a 4-fold rise in titer with respect to pooled baseline sera, and 10/34 with hSBA titers ≥8 and at least a 4-fold rise in titer with respect to baseline. These data confirm MATS as a conservative estimate for predicting strain coverage by 4CMenB.